DOI: 10.11606/d.11.2006.tde-22102007-092659
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da sustentabilidade nutricional de plantios de Pinus taeda L. usando um balanço de entrada-saída de nutrientes

Abstract: DEDICATÓRIA A DEUS e aos meus pais Affonso e Hildaires pelo dom da vida e pelos valores pessoais que norteiam a minha caminhada. Aos meus irmãos, minha irmã e meus sobrinhos por serem a minha bela família e pelo apoio em todos os momentos. A Agnes que me trouxe a Beatrisse Que veio para trazer um novo sentido a vida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
25

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 7 publications
2
4
0
25
Order By: Relevance
“…Evaluating 26-year-old Pinus taeda, Oki (2002) found that wood accounted for roughly 75 % of the tree biomass, the branches 16 %, the needles 6 %, and bark, 3 %. The order of biomass distribution was: wood>root>dead branches>live branches>bark>needles, an order similar to that observed by Bizon (2005) for 25-year-old Pinus taeda in the same soil type.…”
Section: Biomass Samplingsupporting
confidence: 81%
See 4 more Smart Citations
“…Evaluating 26-year-old Pinus taeda, Oki (2002) found that wood accounted for roughly 75 % of the tree biomass, the branches 16 %, the needles 6 %, and bark, 3 %. The order of biomass distribution was: wood>root>dead branches>live branches>bark>needles, an order similar to that observed by Bizon (2005) for 25-year-old Pinus taeda in the same soil type.…”
Section: Biomass Samplingsupporting
confidence: 81%
“…Considering, for example, total N in the biomass, 31 % was found in the roots, 26 % in the litter, 18 % in the wood, 13 % in the needles, 9 % in the branches, and 6 % in the bark. Hence, the crown accounts for roughly 15 % of the biomass and stores 22 % of the total N. The relative nutrient contents accumulated in these components were similar in the results of Bizon (2005).…”
Section: Biomass Samplingsupporting
confidence: 75%
See 3 more Smart Citations